The complex formation of MASP-3 with pattern recognition molecules of the lectin complement pathway retains MASP-3 in the circulation - Kusakari, Kohei; Machida, Takeshi; Ishida, Yumi; Omori, Tomoko; Suzuki, Toshiyuki; Sekimata, Masayuki; Wada, Ikuo; Fujita, Teizo; Sekine, Hideharu (Frontiers in Immunology, 2022)
The complement system plays an important role in host defense and is activated via three different activation pathways. We have previously reported that mannose-binding lectin-associated serine protease (MASP)-3, unlike its splicing variant MASP-1, circulates in an active form and is essential for the activation of the alternative pathway (AP) via the activation of complement factor D (FD). On the other hand, like MASP-1 and MASP-2 of the lectin pathway (LP), MASP-3 forms a complex with the pattern recognition molecules (PRMs) of the LP (LP-PRMs). Both MASP-1 and MASP-2 can be activated efficiently when the LP-PRMs complexed with them bind to their ligands. On the other hand, it remains unclear how MASP-3 is activated, or whether complex formation of MASP-3 with LP-PRMs is involved in activation of MASP-3 or its efficiency in the circulation. To address these issues, we generated wild-type (WT) and four mutant recombinant mouse MASP-3 proteins fused with PA (human podoplanin dodecapeptide)-tag (rmMASP-3-PAs), the latter of which have single amino acid substitution for alanine in the CUB1 or CUB2 domain responsible for binding to LP-PRMs. The mutant rmMASP-3-PAs showed significantly reduced in-vivo complex formation with LP-PRMs when compared with WT rmMASP-3-PA. In the in-vivo kinetic analysis of MASP-3 activation, both WT and mutant rmMASP-3-PAs were cleaved into the active forms as early as 30 minutes in the circulation of mice, and no significant difference in the efficiency of MASP-3 cleavage was observed throughout an observation period of 48 hours after intravenous administration. All sera collected 3 hours after administration of each rmMASP-3-PA showed full restoration of the active FD and AP activity in MASP-3-deficient mouse sera at the same levels as WT mouse sera. Unexpectedly, all mutant rmMASP-3-PAs showed faster clearance from the circulation than the WT rmMASP-3-PA. To our knowledge, the current study is the first to show in-vivo kinetics of MASP-3 demonstrating rapid activation and clearance in the circulation. In conclusion, our results demonstrated that the complex formation of MASP-3 with LP-PRMs is not required for in-vivo activation of MASP-3 or its efficiency, but may contribute to the long-term retention of MASP-3 in the circulation.